Solar photovoltaic array fed water pump driven by brushless DC motor using Landsman converter. Issue 4 (1st April 2016) - Singh, Bhim; Kumar, Rajan
Abstract : This study deals with the use of a Landsman converter for maximum power point tracking in solar photovoltaic (SPV) array‐based water pump driven by a permanent magnet brushless DC (BLDC) motor. The primary function of a DC–DC Landsman converter is to optimise the power output of SPV array and it also provides the safe and soft starting of the BLDC motor with an appropriate control. Amongst various DC–DC converters, Landsman converter meets the desired performance of proposed water pumping system. The starting, dynamic and steady‐state behaviours of the SPV array fed BLDC motor driven water pump are presented to demonstrate the novelty of the proposed system. The SPV fed water pumping system under study is simulated using MATLAB/SIMULINK environment and validated on a developed prototype of the system in order to manifest its performance under practical operating conditions.